The effect of transformational leadership on professional learning communities in Indonesian public high schools - Winda Dewi Listyasari; Devie Yundianto; Yasmin Nabilah Khoirunisa (UIN Raden Mas Said Surakarta, 2026)
Despite extensive research on school leadership, empirical findings regarding the influence of transformational leadership on Professional Learning Community (PLC) practices remain inconsistent, particularly in the Indonesian context. This study aims to examine the effect of transformational leadership on PLC practices in public senior high schools in Central Jakarta, Indonesia. A quantitative correlational design was employed, involving 108 teachers selected through purposive sampling. Data were collected using the Principal Leadership Questionnaire (PLQ) and the Professional Learning Communities Assessment–Revised (PLCA-R). The data were analyzed using regression analysis with the assistance of SPSS. The findings reveal a strong and statistically significant positive effect of transformational leadership on PLC practices (β = 0.912; p < 0.001), indicating that effective leadership behaviors substantially enhance collaborative learning cultures among teachers. Furthermore, transformational leadership accounts for a meaningful proportion of variance in PLC implementation, highlighting its role as a key predictive factor. These results emphasize the importance of strengthening principals’ transformational leadership capacity to foster sustainable professional collaboration and improve educational quality. Consequently, policymakers and educational stakeholders are encouraged to prioritize leadership development programs that emphasize vision-building, teacher support, and collaborative practices within schools.